Climate Cha(lle)nges in global wine production and trade patterns - Emilia Lamonaca; Antonio Seccia; Fabio Gaetano Santeramo (Wine Economics and Policy, 2023)
The global wine trade is interested by significant changes since a few decades, due to new productive scenarios induced by climate change and to (rapidly) evolving trade and policy regimes. We investigate how these changes are altering trade dynamics. Following a gravity-type approach, we find that higher temperatures are beneficial for the terms of trade, and are boosting trade values. As for policy interventions, the impact of technical measures on trade values is heterogeneous across objectives: While technical measures tend to friction trade, the environment-related policies show pro-trade effects.